2020
DOI: 10.7759/cureus.8950
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Statins on Serum Vitamin D Concentrations Among Older Adults

Abstract: Background Randomized and observational studies have previously reported inconsistent results for the direct association between statin therapy and 25, hydroxyvitamin D [25(OH)D] levels. Thus, the present study aimed to examine the relationship between statin use and 25(OH)D and its metabolites concentrations in a large nationally representative sample of older adults. Methods This study was conducted using data from the National Health and Nutrition Examination Survey. Participants were asked to show the medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…It is commonly suggested that 25(OH)D deficiency is linked with increased risk of hyperlipidaemia and cardiovascular disease 49,50 ; however, a recent study in the National Health and Nutrition Examination Survey database found that statin users had significantly higher 25(OH)D levels compared to non-users. 51 We found an association between the statin proxy and lower levels of vitamin D, alkaline phosphatase and calcium, while PCSK9 and LDLR CYP51A1 and interrupt cholesterol biotransformation. 52 It is also possible that HMGCR inhibition inhibits 7-dehydrocholesterol synthesis, which acts as a precursor to both cholesterol and vitamin D. 53 In line with earlier studies by Ference et al 54 and Lotta et al, 55 the HMGCR and NPC1L1 genetic instruments were associated with HbA1c (glycated haemoglobin), an indicator of increased diabetes risk.…”
Section: Discussionmentioning
confidence: 65%
“…It is commonly suggested that 25(OH)D deficiency is linked with increased risk of hyperlipidaemia and cardiovascular disease 49,50 ; however, a recent study in the National Health and Nutrition Examination Survey database found that statin users had significantly higher 25(OH)D levels compared to non-users. 51 We found an association between the statin proxy and lower levels of vitamin D, alkaline phosphatase and calcium, while PCSK9 and LDLR CYP51A1 and interrupt cholesterol biotransformation. 52 It is also possible that HMGCR inhibition inhibits 7-dehydrocholesterol synthesis, which acts as a precursor to both cholesterol and vitamin D. 53 In line with earlier studies by Ference et al 54 and Lotta et al, 55 the HMGCR and NPC1L1 genetic instruments were associated with HbA1c (glycated haemoglobin), an indicator of increased diabetes risk.…”
Section: Discussionmentioning
confidence: 65%
“…However, in a study on patients with hyperlipidemia, they were given 10mg of rosuvastatin led to a significant increase in 25(OH)D levels (33). The exact mechanism of statins effect on 25(OH)D metabolism is not understood, but some researchers have proposed that 7dehydrocholesterol is the precursor of vitamin D and cholesterol, and the inhibition of 3-hydroxy-3methylglutaryl coenzyme A reductase leads to an elevation in 7dehydrocholesterol levels, this may offer a substrate for 25hydroxy vitamin D synthesis (34).…”
Section: Discussionmentioning
confidence: 99%
“…There is no official recommendation for using statin therapy in patients with osteoporosis as the data is very heterogeneous regarding dose-effect correlation, statin effect on sex hormones levels (estradiol and testosterone), and vitamin D levels ( Leutner et al, 2019 ; Thabit et al, 2014 ; Hsia et al, 2002 ; Varri et al, 2016 ; Orces et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%